Angiotensin-Converting Enzyme 2 Activator Ameliorates Severe Pulmonary Hypertension in a Rat Model of Left Pneumonectomy Combined With VEGF Inhibition - Chen, I-Chen; Lin, Jao-Yu; Liu, Yi-Ching; Chai, Chee-Yin; Yeh, Jwu-Lai; Hsu, Jong-Hau; Wu, Bin-Nan; Dai, Zen-Kong (Frontiers in Medicine, 2021)
Background: Pulmonary arterial hypertension (PAH) is a life-threatening and deteriorating disease with no promising therapy available currently due to its diversity and complexity. An imbalance between vasoconstriction and vasodilation has been proposed as the mechanism of PAH. Angiotensin-converting enzyme 2 (ACE2), which catalyzes the hydrolysis of the vasoconstrictor angiotensin (Ang) II into the vasodilator Ang-(1-7), has been shown to be an important regulator of blood pressure and cardiovascular diseases. Herein we hypothesized diminazene aceturate (DIZE), an ACE2 activator, could ameliorate the development of PAH and pulmonary vascular remodeling. Methods: A murine model of PAH was established using left pneumonectomy (PNx) on day 0 followed by injection of a single dose of the VEGF receptor-2 inhibitor SU5416 (25 mg/kg) subcutaneously on day 1. All hemodynamic and biochemical measurements were done at the end of the study on day 42. Animals were divided into 4 groups (n = 6–8/group): (1) sham-operated group, (2) vehicle-treatment group (SuPNx42), (3) early treatment group (SuPNx42/DIZE1−42) with DIZE at 15 mg/kg/day, subcutaneously from day 1 to day 42, and (4) late treatment group (SuPNx42/DIZE29−42) with DIZE from days 29–42. Results: In both the early and late treatment groups, DIZE significantly attenuated the mean pulmonary artery pressure, pulmonary arteriolar remodeling, and right ventricle brain natriuretic peptide (BNP), as well as reversed the overexpression of ACE while up-regulating the expression of Ang-(1-7) when compared with the vehicle-treatment group. In addition, the early treatment group also significantly decreased plasma BNP and increased the expression of eNOS. Conclusions: ACE2 activator has therapeutic potentials for preventing and attenuating the development of PAH in an animal model of left pneumonectomy combined with VEGF inhibition. Activation of ACE2 may thus be a useful therapeutic strategy for the treatment of human PAH.